Effectof Different Feedsand Typesof Feed Thatare Goodor Population Growthand The Biomassof Silk Worms (Tubifexsp.) - Anggraini, Betty; Nuraini, Nuraini; Sukendi, Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis research was conducted on August 8th - October 3rd 2018 at the Laboratory of Fish Hatchery and Breeding, Faculty of Fisheries and Marine Sciences, Riau University. The purpose of this study is to determine the effect of different feeds and types of feed that are good for population growth and the biomass of silk worms (Tubifex sp.). The method used was a completely randomized design (CRD) with 1 factor and 4 treatment levels where each treatment used 3 replications to obtain 12 experimental units. The treatment in this study was the provision of feed with 55g oftofu dregs, 55g of sago dregs, 55gchicken manure and 55g bran against silk worms (Tubifex sp.) The results showed that different feeding significantly (P <0.05) on population growth and silk worm biomass (Tubifex sp.). Giving tofu dregs is the best feed for population growth and silk worm biomass (Tubifex sp.). which resulted in a population growth of 107098 ind, the highest biomass growth was 165.15 g and an increase in length of 1.72 cm. Key Word: Tubifex sp., Different Feed, Population Growth, Biomass Growth